Analyzing Parameters Influencing Scour Bed in Confluence Channels Using Flow3D Numerical Model - Behnam Shamohamadi; Ali Mehboudi (Civil Engineering Journal, 2016)
Channels junction is a phenomenon which is used in most of irrigating and drainage networks and in hydraulic engineering in general. In two channels junction, main and secondary channels encounter with each other and move to the channel downstream. Scour holes and sedimentation zones are created in channels bed. 3D simulation of scour hole created in these channels is influenced by various factors. The ratio of main channel width to secondary channel width is one of the most important influencing factors. This parameter is the main focus of the present research. In the present study, a model calibrated with laboratory results has been simulated. The numerical model results have revealed that decreasing the ratio of main channel width to secondary channel width causes the secondary channel flow encounters to the front wall of the secondary channel. Also, it leads to creating scour near the front wall and the main hole is drawn towards the wall. Furthermore, in the present research, topographical changes of the bed with running time of the numerical model for the middle channel axis has been extracted and presented.